Multimodal large language models for bioimage analysis - Zhang, Shanghang; Dai, Gaole; Huang, Tiejun; Chen, Jianxu (Nature methods, 2024)
Multimodal large language models have been recognized as a historical milestone in the field of artificial intelligence and have demonstrated revolutionary potentials not only in commercial applications, but also for many scientific fields. Here we give a brief overview of multimodal large language models through the lens of bioimage analysis and discuss how we could build these models as a community to facilitate biology research.